2020
DOI: 10.1128/mbio.01340-20
|View full text |Cite
|
Sign up to set email alerts
|

New Multidrug Efflux Inhibitors for Gram-Negative Bacteria

Abstract: Active efflux of antibiotics preventing their accumulation to toxic intracellular concentrations contributes to clinically relevant multidrug resistance. Inhibition of active efflux potentiates antibiotic activity, indicating that efflux inhibitors could be used in combination with antibiotics to reverse drug resistance. Expression of ramA by Salmonella enterica serovar Typhimurium increases in response to efflux inhibition, irrespective of the mode of inhibition. We hypothesized that measuring ramA promoter a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 55 publications
(83 reference statements)
0
21
0
2
Order By: Relevance
“…Examples of non-essential target inhibitors are represented by: Inhibitors of virulence-conferring factors or pathways (also known as anti-virulence compounds or pathoblockers 86 that target, for example, quorum sensing mechanisms 87 , biofilm formation 88 , bacterial secretion systems 89 , 90 , enzymes for tissue penetration 91 or intracellular survival 92 ). Efflux pump inhibitors 93 . Suicide substrates such as β-lactamase inhibitors 94 , 95 .…”
Section: Synthetic Hit Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of non-essential target inhibitors are represented by: Inhibitors of virulence-conferring factors or pathways (also known as anti-virulence compounds or pathoblockers 86 that target, for example, quorum sensing mechanisms 87 , biofilm formation 88 , bacterial secretion systems 89 , 90 , enzymes for tissue penetration 91 or intracellular survival 92 ). Efflux pump inhibitors 93 . Suicide substrates such as β-lactamase inhibitors 94 , 95 .…”
Section: Synthetic Hit Compoundsmentioning
confidence: 99%
“…These factors can be addressed by suitable compound design, which generally remains rather empirical and challenging 254 257 . Other possibilities to address this key area would be to use these compounds in combination with outer membrane permeabilizing agents 258 , 259 or efflux inhibitors 93 , 260 . Alternative approaches targeting extracellular virulence factors, for example, extracellular lectins required for attachment and biofilm formation or secreted proteolytic enzymes, do not suffer from a possible lack of bacterial uptake 261 .…”
Section: Advancing Hits To (Pre)clinical Statusmentioning
confidence: 99%
“…Of the EIs identified, auranofin ( 8 , Figure 56 ), an antirheumatic agent, increased ethidium bromide accumulation and potentiated antibiotic activity in checkerboard assays. 898 While most drug screening efforts have focused on looking at inhibitors of RND inner membrane transporters, a recent study identified an inhibitor of the ABC type efflux pump MacAB in S. Typhimurium. Compound 9 ( Figure 56 ) was identified from screening a drug library for compounds that inhibited the growth of a macAB -overexpressing strain in the presence of erythromycin.…”
Section: Targeting Tripartite Assemblies—pump Inhibitors and Disruptorsmentioning
confidence: 99%
“…So when a substance activates ramA, the fluorescent protein is produced and the researchers can see the glow using high-throughput screening machinery. The team has now screened nearly 50,000 compounds, identifying 43 efflux-pump inhibitors, 11 of which have been shown to increase the efficacy of antibiotics in lab tests 2 .…”
Section: Top Targetsmentioning
confidence: 99%